Comparison between two methods of power training on swimming performance - Elrakhawy, M. I. I. (American Journal of Sports Science, 2023)
The aim of the research is to a comparison between two methods of power training, strength-speed and speed-strength on the performance of 50-meter freestyle swimming. The experimental method was applied to a sample of 12 adult swimmers (mean +/-SD: 16 +/-1 year, 172.2+/-3.2cm, 78.2+/-2.3kg) divided into two experimental groups, group A (strength-speed) and group B (speed-strength) by applying pre-and post-measurements,1RM bench press, 1RM squat, medicine ball chest throw, vertical jump, stroke length (SL), stroke rate (SR) and 50-meter freestyle tests was applied on the subjects respectively, Statistical Analyses Repeated-measures analysis of variance (ANOVA) was used to compare 50-meter freestyle trial time performance after the 2 different power training methods. Statistical significance was accepted at (p <0.05), (p <0.01). A 6-week power training program was applied 3 times a week, results show significant differences between pre and post-measurements in stroke length (t=3.64) and stroke rate (t=7.00) in group A, 1RM squat (t=3.60), vertical jump (t=4.96), stroke length (t=6.76) and 50-meter freestyle (t=32.91) in group B, and non-significant differences in 1RM bench press (t=2.33), 1RM squat (t=2.22), chest MD ball throw (t=2.35), vertical jump (t=2.18), and 50-meter freestyle (t=1.93) in group (A),1RM bench press (t=2.61), chest MD ball throw (t=2.08) and stroke rate (t=1.40) in group (B) for post-measurements. Present results recommend that dry-land program training must include the two methods of power training, strength-speed, and speed-strength, based on the force-velocity relationship for sprint swimmers during a specific period, power training in these two methods improves stroke length, and stroke rate and it leads to enhance swimming performance in sprint events.